2012
DOI: 10.1890/11-1210.1
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal subsidies between freshwater and terrestrial ecosystems structure consumer resource dynamics

Abstract: Cross-ecosystem movements of material and energy, particularly reciprocal resource fluxes across the freshwater-land interface, have received major attention. Freshwater ecosystems may receive higher amounts of subsidies (i.e., resources produced outside the focal ecosystem) than terrestrial ecosystems, potentially leading to increased secondary production in freshwaters. Here we used a meta-analytic approach to quantify the magnitude and direction of subsidy inputs across the freshwater-land interface and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
168
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 63 publications
9
168
0
2
Order By: Relevance
“…Our findings show that these managementinduced disturbances (or preventions thereof) can directly affect dynamics in spatially coupled ecosystems, such as rivers or lakes, which are fed by resources from these 'green' ecosystems [7,[46][47][48][49]. We experimentally demonstrated, and showed also in a mathematical model, that the direction of the effects depend on the temporal unfolding, the magnitude of disturbance and the type of connected ecosystems (autotrophic versus heterotrophic dominated).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our findings show that these managementinduced disturbances (or preventions thereof) can directly affect dynamics in spatially coupled ecosystems, such as rivers or lakes, which are fed by resources from these 'green' ecosystems [7,[46][47][48][49]. We experimentally demonstrated, and showed also in a mathematical model, that the direction of the effects depend on the temporal unfolding, the magnitude of disturbance and the type of connected ecosystems (autotrophic versus heterotrophic dominated).…”
Section: Discussionmentioning
confidence: 56%
“…The actual prevalence of meta-ecosystems in natural landscapes is currently unknown but evidence suggests that they might be ubiquitous to certain ecosystem boundaries [7,23]. The feedback between demography, perturbations and changes in cross-ecosystem subsidy exchanges that we demonstrated here suggests that meta-ecosystem dynamics might be even more significant within fragmented and altered landscapes [54].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Aquatic and riparian ecosystems are connected by fluxes of energy and matter. For example, terrestrially derived carbon and nutrients support aquatic metabolism (Wallace et al, 1999;Mehner et al, 2005) while emerging aquatic insects and amphibians provide subsidies for a wide range of terrestrial consumers (Marczak and Richardson, 2007;Bartels et al, 2012). Aquatic-terrestrial subsidy fluxes can be reciprocal, benefitting consumers in both habitats (Polis et al, 1997;Nakano and Murakami, 2001;Richardson et al, 2010) while also contributing to food-web and ecosystem stability (Takimoto et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research that Nakano participated in or inspired has addressed the spatial and temporal heterogeneity of invertebrate subsidies and how it influences the distribution of predators like birds and spiders at different spatial scales (Iwata et al , 2010Iwata 2007;Uesugi and Murakami 2007), and new research has revealed how spatial subsidies of invertebrates stabilize resource fluxes in spatially and thermally heterogeneous river-tributary networks (Uno and Power 2015;Uno 2016). Recent meta-analyses have shown that fish predation reduces adult aquatic insects that emerge to feed terrestrial predators by about 40% (Wesner 2016), and that even though the flux of terrestrial prey to streams is nearly an order of magnitude higher than aquatic prey to riparian zones, the contribution of aquatic prey to terrestrial predators is apparently much higher than of terrestrial prey to aquatic predators (Bartels et al 2012).…”
Section: Linkages Between Terrestrial and Aquatic Ecosystems In Foresmentioning
confidence: 99%